Cardiopulmonary Bypass Induces Acute Lung Injury via the High-Mobility Group Box 1/Toll-Like Receptor 4 Pathway. (25th September 2020) - Deng, Yuxiao; Hou, Lei; Xu, Qiaoyi; Liu, Qi; Pan, Su; Gao, Yuan; Dixon, Richard A. F.; He, Zhengyu; Wang, Xiangrui
Abstract : During cardiopulmonary bypass (CPB), pulmonary ischemia/reperfusion (I/R) injury can cause acute lung injury (ALI). Our previous research confirmed that abnormal high-mobility group box 1 (HMGB1) release after CPB was closely related to ALI. However, the mechanism underlying the HMGB1-mediated induction of ALI after CPB is unclear. Our previous study found that HMGB1 binds Toll-like receptor 4 (TLR4), leading to lung injury, but direct evidence of a role for these proteins in the mechanism of CPB-induced lung injury has not been shown. We examined the effects of inhibiting HMGB1 or reducing TLR4 expression on CPB-induced lung injury in rats administered anti-HMBG1 antibody or TLR4 short-hairpin RNA (shTLR4), respectively. In these rat lungs, we studied the histologic changes and levels of interleukin- (IL-) 1 β, tumour necrosis factor- (TNF-) α, HMGB1, and TLR4 after CPB. After CPB, the lung tissues from untreated rats showed histologic features of injury and significantly elevated levels of IL-1 β, TNF- α, HMGB1, and TLR4. Treatment with anti-HMGB1 attenuated the CPB-induced morphological inflammatory response and protein levels of IL-1 β, TNF- α, HMGB1, and TLR4 in the lung tissues and eventually alleviated the ALI after CPB. Treatment with shTLR4 attenuated the CPB-induced morphological inflammatory response and protein levels of IL-1 β, TNF- α, and TLR4 in the lung tissues and eventually alleviated the ALI after CPB, but could not alleviate the HMGB1 protein levels induced by CPB. In summary, the present study demonstrated that the HMGB1/TLR4 pathway mediated the development of ALI induced by CPB.